Afganistan medyasının rekabet yapısı - Shaheen, Abdul Rasool (My University, 2021)
AFGANİSTAN MEDYASININ REKABET YAPISI Afganistan medyası, tarihinde ülkenin siyasal örgütlenme yapısını şekillendiren Mücahitler, Taliban ve Cumhuriyet Dönemleri olmak üzere geçmişten günümüze küresel ve siyasi gelişmelere bağlı olarak ortaya çıkan “Otoriter Medya Kuramı”, “Liberal/ Neo-liberal Medya Kuramı”, “Sosyal Sorumluluk Kuramı” ve “Sovyet-Komünist Medya Kuramı” modellerine uygun biçimler almıştır. Afganistan tarihinde basına ilk adım, Emir Şir Ali Han zamanında 1873 yılında atılmış ve gazete yayınlanmaya başlanmıştır. O zamanlar, komşu ülkelerde hiç benzeri olmayan matbaacılıktan gazeteciliğe ve ifade özgürlüğünden basın yasasının çıkarılmasına kadar çeşitli alanlarda gelişmelerin olduğu görülmektedir. Daha sonra ilk kez 1919-1929 yılları arasında, Emir Amanullah Han zamanında gazetecilik alanında basın yasası ve ifade özgürlüğü yasasının yayınlanmasıyla toplam 22 gazetenin yayınlandığı görülmektedir. 2001 yılından günümüze, Afganistan İslam Cumhuriyeti dönemi olarak ülke genelinde, 400’den fazla basılı yayın, yaklaşık 150 radyo istasyonu ve 75’ten fazla televizyon kanalının bulunduğu görülmektedir. Bu medya kuruluşlarının, Afganistan piyasasında gruplaşarak genişlediği görülmektedir. Bu kuruluşların yanında farklı etnik, siyasi ve dini kesimlere ait medya ve basın grupları da bulunmaktadır.

COMPETITION STRUCTURE OF AFGHANISTAN MEDIA Afghanistan media, “Authoritarian Media Theory”, “Liberal/ Neo-liberal Media Theory”, “Social Responsibility Theory” and “Authority Media Theory”, which have emerged depending on global and political developments from past to present, including Mujahideen, Taliban and Republican Periods that have shaped the political organizational structure of the country in its history that has taken forms in accordance with the models. The first step to the press in the history of Afghanistan was taken in 1873 at the time of Emir Shir Ali Khan and the newspaper started to be published. At that time, it was seen that there were developments in various fields, from printing to journalism and the freedom of expression to the press law, which were unprecedented in neighboring countries. Later on, for the first time between 1919-1929, with the publication of the press law and freedom of expression law in the field of journalism during Emir Amanullah Khan’s time, it is seen that a total of 22 newspapers were published. From 2001 to present, throughout the country as the period of the Islamic Republic of Afghanistan, it is seen that there are more than 400 printed publications, approximately 150 radio stations, and more than 75 television channels. It is seen that these media organizations are expanding by grouping in the Afghan market. In addition to these organizations, there are also media and press groups belonging to different ethnic, political and religious segments.
Keywords: Afganistan; Afganistan Medyasının Rekabet Yapısı; Afghanistan; Basın; Competition Structure of Afghanistan Media; Kitle iletişim araçları; Mass media; Media andCompetition; Medya ve Rekabet; Press